ANALISIS PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN DAN KEPUASAN KERJA DENGAN VARIABEL MODERATOR KOMITMEN PADA PT PLN (PERSERO) UNIT INDUK PEMBANGUNAN JAWA BAGIAN TIMUR DAN BALI I - sigit prasetyo (Jurnal Ilmu Manajemen (JIMMU), 2020)
AbstractThe sample used is 194 employees of PT PLN (Persero) Main Unit Development of East Part Network and Bali I (UIP JBTB I). The result of analysis by using SEM indicates that 1) Motivation has a positive effect posittif on employee performance of PT PLN (Persero) Main Unit of Development of Eastern Part Network and Bali I (UIP JBTB I). 2) Motivation has a significant positive effect on job satisfaction at PT PLN (Persero) Main Unit of Development of Eastern Part Network and Bali I (UIP JBTB I). 3) Commitment to strengthen the influence of motivation on employee performance of PT PLN (Persero) Main Unit of Development of Eastern Part Network and Bali I (UIP JBTB I). 4) Commitment to weaken the influence of motivation on employee satisfaction PT PLN (Persero) Main Unit Development of Eastern Part Network and Bali I (UIP JBTB I).  Keywords: Motivation, employee, Commitment AbstractThe sample used is 194 employees of PT PLN (Persero) Main Unit Development of East Part Network and Bali I (UIP JBTB I). The result of analysis by using SEM indicates that 1) Motivation has a positive effect posittif on employee performance of PT PLN (Persero) Main Unit of Development of Eastern Part Network and Bali I (UIP JBTB I). 2) Motivation has a significant positive effect on job satisfaction at PT PLN (Persero) Main Unit of Development of Eastern Part Network and Bali I (UIP JBTB I). 3) Commitment to strengthen the influence of motivation on employee performance of PT PLN (Persero) Main Unit of Development of Eastern Part Network and Bali I (UIP JBTB I). 4) Commitment to weaken the influence of motivation on employee satisfaction PT PLN (Persero) Main Unit Development of Eastern Part Network and Bali I (UIP JBTB I).  Keywords: Motivation, employee, Commitment